Biofuels : production, application and development - Scragg, A. H. 1943- (CABI, 2009)
This book contains 8 chapters presenting an outline of the problems associated with fossil fuel use, and discusses the consequences of burning fossil fuels as well as how the adoption of alternative fuels can mitigate global warming. Other chapters cover biologically produced, solid, gaseous and liquid biofuel production with their advantages and disadvantages.